Factors leading to reluctance of blood donors from blood donation in Derna/Libya - Elzahaf, Raga A.; Khalil, Khalid A.; Alshareff, Hawwa; Bufajra, Amnah (International Journal Of Community Medicine And Public Health, 2023)
Background: Blood donation is a major concern to the society as donated blood is lifesaving for individuals who need it. In Libya, the concept of voluntary blood donors is almost non-existent due to the absence of blood donor motivation and retention strategies. The objective of this study was to assess the factors leading to reluctance of blood donors from blood donation blood donation among general population in Derna. Methods: Descriptive cross-sectional survey design was used to collect data of barriers towards blood donation in Derna/Libya between August 2021 and September 2021. 425 Libyan living in the city of Derna were selected by convenience sampling design. Self-administered structured questionnaire was used which was adopted from previous studies. Data analysis was performed in statistical package for the social sciences (SPSS) version 25. Results: Of the 425 participants, the majority of them were male (70.1%). 195 (45.9%) reported that they had donated blood at least once in their lifetime, 186 (95.4%) were male and 9 (4.6%) were female. People who never donated blood most commonly (54.1%) reported that they never donated because they did not feel comfortable in hospital, followed by blood donation causes weakness and fainting or dizzy and they have never been asked to donate. Conclusions: Blood donation practice in this study was found to be low. Ministry of health and Red Cross association have to work in strengthen manner to improve the practice of blood donation to plan strategy of awareness about blood donation should be encouraged among general population.